Technology adoption as a pathway to financial inclusion in the digital economy: A study of Indonesian SME’s - Febriyanti, Intan Rike; Herdiani, Herni; Gunawan, Ce; Zahra, Zalfa Alifah (Jurnal Mantik, 2026)
Financial inclusion remains a pressing challenge for Indonesian MSMEs, with nearly 70% of enterprises still facing limited access to formal financial services. In the era of rapid digital transformation, the digital economy presents an opportunity to reduce this gap by enabling broader access through technology-driven platforms. This study aims to examine the influence of the digital economy on financial inclusion, as well as to investigate the mediating role of technology adoption based on the Technology Acceptance Model (TAM). Utilizing a quantitative research design, data were collected through a validated questionnaire from 350 MSME actors in Sukabumi, Indonesia. Structural Equation Modeling using Partial Least Squares (SEM-PLS) was applied to analyze both the measurement and structural models. The results reveal that the digital economy significantly affects both financial inclusion and technology adoption. Furthermore, technology adoption has a positive and significant impact on financial inclusion, and also serves as a partial mediator between the digital economy and financial inclusion. These findings underscore the critical role of behavioral acceptance in the successful implementation of digital financial services. This study contributes to the development of an integrated framework that combines structural and behavioral perspectives, offering practical insights for policymakers and digital service providers aiming to foster inclusive economic growth through technology-driven financial access.